Improved navigation-based motion compensation for LFMCW synthetic aperture radar imaging. Issue 2 (February 2016) - Saeedi, Jamal; Alavi, Seyed
Abstract In this paper, a new motion compensation algorithm using navigation data is proposed for frequency domain algorithm of synthetic aperture radar (SAR) imaging. SAR processing method assumes that the sensor is moving in a straight line at a constant speed; however in reality, a SAR platform will deviate from this ideal. This non-ideal motion can seriously degrade the SAR image quality. In this study, the linear frequency-modulated continuous wave SAR signal model is presented. The effects of non-ideal motion during the SAR signal modeling are investigated, and new method for motion correction is developed. This new motion compensation algorithm is verified with simulated data and with actual data collected using FMCW mode SAR dataset.